PENANAMAN DAN PENINGKATAN NILAI KEDISIPLINAN DI SD PERTIWI MAKASSAR - Muhammad Ikbal; Syarifah Aeni Rahman; Siti Martieni (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
Student discipline has a very important role in the learning process at school. Students who are not accustomed to discipline and are not handled by the school immediately, will develop habits in themselves so that they always commit violations of every existing rule. Efforts made by schools to discipline students are the existence of rules that are made so that these regulations can be obeyed. However, the existing rules at school are only used as a display without wanting to apply them concretely. So from this it is necessary to instill the value of discipline in schools, namely by giving light punishments so that students will not repeat the violation a second time. This research is a literature review research with a descriptive approach. The literature reviewed in this study comes from research journals. The conclusion in this study shows that the inculcation of discipline at SD Pertiwi Makassar has gone quite well, but still needs to be improved